METODE GENERALIZED SPACE-TIME AUTOREGRESSIVE UNTUK PERAMALAN PERTUMBUHAN EKONOMI DI KAWASAN TIMUR INDONESIA - Rokhana Dwi Bekti; Noviana Pratiwi; Petronella Mira Melati (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2018)
Generalized Method of Space Time Autoregressive (GSTAR) is one of spatio temporal method. This method modifies the spatial dependencies among location by using the time series data or time lags. This research applies the GSTAR for forecasting economic growth in Eastern Indonesia. The economic development of some provinces in the region, which is far from state of capital, is highly dependent on access to the facility centers of economic activity, access to education, access to health facility, and others. Thus forecasting information by taking into account the spatial aspect (the relationship between the provinces) and time is needed to assess the economic development of several periods ahead. GSTAR (1;1) was selected for the forecasting. Parameter estimation using least squares build the different parameter in each province. Based on comparisons with ARIMA method, GSTAR provide better forecasting results.